PENGARUH PEMBERIAN PUPUK BOKASHI FESES KUDA SANDALWOOD TERHADAP PRODUKTIVITAS SESBANIA GLANDIFLORA - Titus Tanga Daku Oru; Marselinus Hambakodu (Universitas Kristen Wira Wacana Sumba, 2022)
The experiment aims to determine the effect of giving bokashi fertilizer of sandalwood horse feces on the productivity of the Sesbania glandiflora. The experiment used experimental method by randomized block design (RBD), 5 treatments and 4 replications such us P0: without bokashi fertilizer of sandalwood horse feces, P1: bokashi fertilizer of sandalwood horse feces 200 gram/planting hole, P2: bokashi fertilizer of sandalwood horse feces 500 gram/planting hole, P3: sandalwood horse feces fertilizer 800 gram/planting hole, P4: bokashi fertilizer of sandalwood horse feces 1.000 gram/planting hole. The variables observed consisted of plant height, total leaves, stem diameter, fresh matter production, and dry matter production. The results showed that the application of bokashi fertilizer sandalwood horse had significant effect (p<0,05) on plant height, total leaves, fresh matter production and dry matter production. Conclusion, the application of bokashi fertilizer of sandalwood horse feces with a level of 800 grams/planting hole was able to provide good growth on Sesbania glandiflora.